Public house reform - Lawson, William (Statistical and Social Inquiry Society of Ireland, 1912)
The writer of an article in our leading journal (1) says:?"The need of the moment is not to abolish the public-house, but to reform it. The first step is to give a very substantial preference in treatment to houses which supply food over those that are only drinking dens. The object must be to supply a place of rational entertainment where a decent man can have a drink in peace, in company with his wife and children." These observations were made in commenting on the statistics of drunkenness in Dublin referred to by Mr. Justice Dodd at the opening of the City Commission at Green Street on February 1st, 1911. It was reported to him that, in the two months which had elapsed since the December Commission, there were 498 cases of drunkenness, as against 372 during the corresponding period in 1909. Notwithstanding that he was assured by the police that drunkenness was on the decline in the city.
Read, Monday, February 27, 1911
Keywords: Public houses; Temperance; 314.15